Fournier’s Gangrene as a Postoperative Complication of Inguinal Hernia Repair - Tolga Dinc; Selami Ilgaz Kayilioglu; Isa Sozen; Baris Dogu Yildiz; Faruk Coskun (Case Reports in Surgery)
Fournier’s gangrene is the necrotizing fasciitis of perianal, genitourinary, and perineal regions. Herein, we present a case of scrotal Fournier’s gangrene as a postoperative complication of inguinal hernia repair. A 51-year-old male with giant indirect hernia is presented. Patient underwent inguinal hernia repair, and after an unproblematic recovery period, he was discharged. He applied to our outpatient clinic on the fifth day with swollen and painful scrotum and it turned out to be Fournier’s gangrene. Polypropylene mesh was not infected. Patient recovered and was discharged after repeated debridements. Basic principles in treatment of Fournier’s gangrene are comprised of initial resuscitation, broad-spectrum antibiotics therapy, and early aggressive debridement. In the management of presented case, aggressive debridement was made right after diagnosis and broad-spectrum antibiotics were given to the hemodynamically stable patient. In these circumstances, the important question is whether we could prevent occurrence of Fournier’s gangrene.